Molecular titanium nitrides: nucleophiles unleashed. Issue 2 (11th October 2016) - Grant, Lauren N.; Pinter, Balazs; Kurogi, Takashi; Carroll, Maria E.; Wu, Gang; Manor, Brian C.; Carroll, Patrick J.; Mindiola, Daniel J.
Abstract : Reactivity studies of a rare example of a molecular titanium nitride are presented. A combination of theory and NMR spectroscopy provide a description of the bonding in the these nitrides, the role of the counter cation, K +, as well as the origin of their highly downfield 15 N NMR spectroscopic shifts. Abstract : In this contribution we present reactivity studies of a rare example of a titanium salt, in the form of [μ2 -K(OEt2 )]2 [(PN)2 TiN]2 (1 ) (PN − = N -(2-(diisopropylphosphino)-4-methylphenyl)-2, 4, 6-trimethylanilide) to produce a series of imide moieties including rare examples such as methylimido, borylimido, phosphonylimido, and a parent imido. For the latter, using various weak acids allowed us to narrow the p K a range of the NH group in (PN)2 TiNH to be between 26–36. Complex1 could be produced by a reductively promoted elimination of N2 from the azide precursor (PN)2 TiN3, whereas reductive splitting of N2 could not be achieved using the complex (PN)2 TiNNTi(PN)2 (2 ) and a strong reductant. Complete N-atom transfer reactions could also be observed when1 was treated with ClC(O) t Bu and OCCPh2 to form NC t Bu and KNCCPh2, respectively, along with the terminal oxo complex (PN)2 TiO, which was also characterized. A combination of solid state 15 N NMR (MAS) and theoretical studies allowed us to understand the shielding effect of the counter cation in dimer1, the monomer [K(18-crown-6)][(PN)2 TiN], and the discrete salt [K(2, 2, 2-Kryptofix)][(PN)2 TiN] as well as the origin of the highly downfield 15 N NMR resonance when shifting from dimer to monomer to a terminal nitride (discrete salt). The upfield shift of 15 Nnitride resonance in the 15 N NMR spectrum was found to be linked to the K + induced electronic structural change of the titanium-nitride functionality by using a combination of MO analysis and quantum chemical analysis of the corresponding shielding tensors.